Dismay as ancient heritage sites across Iran damaged in US-Israel bombing - Borger, Julian; Parent, Deepa (The Guardian, 2026)
Golestan Palace world heritage site in Tehran and palace in Isfahan harmed despite Unesco sending coordinates.
Keywords: Architecture; Art and design; Culture; Heritage; Iran; Middle East and north Africa; US-Israel war on Iran; Unesco; United Nations; World news